The Influence of Media on Public Perspectives on the Causes of Floods - Anggun Tri Kurniawatik; Aura Doa Apriliansyah; Vindy Iq Refianty (The International Journal of Politics and Sociology Research, 2021)
This study aims to see the effectiveness of society in seeing a phenomenon in the environment specifically flooding. But this can be supported or inhibited by the point of view of a media. The media becomes one of the sources trusted by the public, so that any information that is aired will affect the psychological community that enjoys the show. In the aspect of natural disasters, this will affect people's attitude towards government policy in the disaster mitigation process. So the media needs to pay attention to every information submitted must be completely siding with the public. This is also included in the condition of the people of Bandung Regency which is often hit by hydrometeorological natural disasters such as floods.